Contentment among religious individuals: An exploratory factor analysis - Rodrigues, Lavina S. (Animo Repository, 2019)
This present study aimed to explore the experience of contentment among religious priests and nuns. An exploratory factor analysis (EFA) was conducted on the responses of 358 religious individuals on a 100-item questionnaire, developed from interviews conducted with 29 religious individuals on how they experience contentment in their lives. Results suggest that a four-factor structure– characterized by pursuing purpose, accepting and actualizing self, belonging in the community, and receiving affirmation from others– describe the experience and components of contentment among religious. Limitations of the study and suggestions for future directions are also discussed.